Participatory mapping of ecosystem services across a gradient of agricultural intensification in West Kalimantan, Indonesia - Mathys, A.S.; van Vianen, J.; Rowland, D.; Narulita, S.; Palomo, I.; Pascual, U.; Sutherland, I.J.; Ahammad, R.; Sunderland, T.C.H. (Informa UK Limited, 2023)
Agrarian change affects the supply and demand of ecosystem services (ES) by reducing the extent of natural ecosystems. Agricultural intensification can lead to changes in land covers and livelihood opportunities and it remains unclear how such changes align or misalign with the desires of local communities. Using participatry mapping, we assessed ES uses and desires of Indigenous people and local communities provided by different land cover types along a gradient of agricultural intensification (forest subsistence, agroforestry mosaic, and monoculture and market-dependence) in West Kalimantan, Indonesia. We found that mapped ES use diversity was highest in the forest-dependent zone and lowest near monoculture agricultural systems. The expressed ES uses and desires varied greatly among land cover types amidst loss of old-growth forest and greater reliance on secondary forest and shrub land. The spatial analysis showed that high priority areas of ES use was related to access in the landscape, demonstrating the importance of attending to place-based social values in ES assessments. From this study, we call for a people-centric spatial modelling approach to address the divergence of social and cultural ES values associated with land covers under different intensification contexts. Participatory mapping clarifies the ES desires of local communities, which state policy often fails to address. We recommend a place specific management strategy to reduce ES trade-offs of specific land use practices, which are currently apparent with agrarian change in Indonesia and relevant for other tropical developing countries.